The Childhood Kingdoms: Imaginaries of Dictatorial Power in Chilean Poetry for Children During the 70s [Os Reinos Da Infância: Imaginários Do Poder Ditatorial Na Poesia Infantil Chilena Dos Anos 70 [Los Reinos de la Infancia: Imaginarios del Poder Dictatorial en la Poesía Chilena Para Niños Durante Los Años Setenta] - Jeftanovic-Avdaloff, A; Vesely-Avaria, C (Universidad Nacional de Colombia, 2021)
This study is framed in the field of children poetry during the 1970s in Chile, taking as a reference the work of the musician and poet Sergio Vesely during his captivity in several detention centers of the military dictatorship. Starting from a critical and theoretical reading, I explored the articulation of symbolic imageries referring to dictatorial power transmitted to children through the metaphor of the king. This work aims to the rescue and making visible forgotten voices, contributing to the construction of a historical memory that integrates new pieces into the map of artistic creation arising from the prison experience in Chile. At the same time, the aim is to contribute to the necessary legitimation of the role of children in historical and social processes, in this case by exploring the imagery transmitted about the exercise of power during the early years of the Chilean dictatorship. © 2021, Universidad Nacional de Colombia. All rights reserved.